Systematic Literature Review: Perbandingan Kinerja Keuangan Bank Syariah Dan Bank Konvensional Di Indonesia - Pauly Demanda (Al-Hilali: Jurnal Perbankan dan Ekonomi Islam, 2026)
This study aims to analyze the comparison of financial performance between Islamic banks and conventional banks in Indonesia. The method used is a Systematic Literature Review (SLR), which identifies and analyzes relevant literature comparing the financial performance of both types of banks during the 2020-2025 period. The main focus of the analysis is on financial ratios such as Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM). The results indicate that although Islamic banks have more stable long-term performance with profit-sharing principles, conventional banks are more flexible in managing liquidity and adapting more quickly to economic changes. This research provides deeper insights into the advantages and challenges of each type of bank in facing the economic dynamics in Indonesia.